Optorheological thickening under the pulsed laser photocrosslinking of a polymer - Okoniewski, Stephen Richard; Wisniewski, Danielle; Frazer, N. Laszlo; Mu, Weiqiang; Arceo, Andrew; Rathi, Pranjali; Ketterson, J. B. (Journal of applied polymer science, 2014)
ABSTRACT Electro‐, magneto‐, and other rheological effects can be used to externally control fluid viscosity. However, they are largely reversible and in addition subject to colloidal settling, electrostatic breakdown, or high cost. In the experiments described here the dependence of the viscosity of a polymer solution under pulsed laser photocrosslinking as a function of radiation dose is determined using the Brownian motion of colloidal polystyrene tracers that were optically confined to a one dimensional channel. The system studied was a transparent aqueous solution of poly(ethylene glycol) dimethacrylate together with a 1‐hydroxycyclohexyl phenyl ketone photoinitiator. An increase in the viscosity of the solution with the laser fluence was observed. The growth was exponential, stable between pulses, and spanned nearly three orders of magnitude. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40690.